Democratization and Human Security in Postwar Sierra Leone
XI, 265 p.
Keywords: This edited collection is the first book-length project to undertake a multidisciplinary study of democratization and human security in the post war nation of Sierra Leone. The overarching theme is there is synergy of democratization and human security which makes it imperative for the state to foster and enhance the realization of these concepts in postwar Sierra Leone. The book is divided into two broad thematic sections. The first section deals with democratization with a critical examination of the creation and instrumentality of institutions largely considered a necessity for democracy to take hold in a country. The second section delineates human security or the lack thereof in key areas of political, social and economic life. Though the book is specific to Sierra Leone, African countries and indeed countries transitioning to democracy around the world, scholars and practitioners of postwar or democratic transition studies would benefit from the concepts expounded in this collection.